Pengaruh Experiential Marketing Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi - Adhitya Yoga Prasetya; Dhian Andanarini Minar Savitri; Budi Kurniawan (CV. ALIM'SPUBLISHING, 2023)
The purpose of this research is to analyze the relationship between Experiential Marketing and Customer Loyalty with Customer Satisfaction as an intervening variable. The independent variable analyzed in this study is Experiential Marketing. The dependent variable analyzed in this study is Customer Loyalty. The intervening variable in this study is customer satisfaction. The sample used in this study consisted of 100 Yamaha Motor Indonesia customers. Sampling was carried out by purposive sampling method by distributing questionnaires. Data analysis in this study used the Structural Equation Modeling (SEM) analysis method. Data analysis in this study used discriminant validity tests, reliability tests, model quality tests, and hypothesis testing with the help of SmartPLS 3 data processing software. The results showed that Experiential Marketing had a positive and significant effect on Customer Loyalty, Experiential Marketing also had a positive and significant effect on Customer Satisfaction and Customer Satisfaction had a positive and significant effect on Customer Loyalty. The other result of this study is that Experiential Marketing has a positive and significant influence on Customer Loyalty through Customer Satisfaction as an intervening variable